Monoclonal antibody H9/25 reacts with functional subsets of T and B cells: killer, killer precursor and plaque-forming cells. - Takei, F; Waldmann, H; Lennox, E; Milstein, C (1980)
Monoclonal antibody (McAb) H9/25 has previously been shown to react with an alloantigen expressed on subpopulations of mouse lymphocytes. We here investigated the expression of the antigen (H9/25 Ag) on functional subsets of T and B cells. Lymphocytes were depleted of H9/25 Ag-bearing cells by complement-dependent cytolysis or by the affinity to immobilized McAb H9/25, and the residual immunological functions were tested. In these tests, killer T cells generated in mixed lymphocyte cultures and their precursors were found to express H9/25 Ag. In contrast, the activity and frequency of helper T cells specific to keyhole limpet hemocyanin carrier were not decreased by the depletion of H9/25 Ag-bearing cells. On the other hand, IgG and IgM anti-TNP plaque-forming cells were found to express H9/25 Ag, while it was not detected on unprimed B cells, as tested by using TNP-Ficoll and TNP-lipopolysaccharide. Only a small proportion of TNP memory B cells seemed to express the antigen. These results revealed significant differences between H9/25 Ag and other known alloantigens in the distribution among functional subsets of lymphocytes.